Clinical and Endoscopic Features and Treatment Aspects of Gastroduodenal Pathology in Patients with Chronic Kidney Disease - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
In recent years, growing attention has been given to the study of gastroduodenal pathology in patients with chronic kidney disease (CKD). This review highlights the prevalence, morphology, diagnosis, and treatment of these disorders. Chronic gastritis, erosive gastroduodenitis, and ulcerative lesions are frequently observed in CKD, particularly in advanced stages, often with few or nonspecific symptoms. Endoscopic findings commonly reveal lymphocytic chronic gastritis and multiple antral erosions. The role of Helicobacter pylori infection remains debated, with variable detection rates among dialysis and pre-dialysis patients. The Maastricht triple-therapy regimen—clarithromycin, amoxicillin, and a proton pump inhibitor—remains effective, though dosing should be adjusted for renal function. Given the risk of complications such as bleeding and perforation, individualized therapeutic and preventive approaches are essential. Further research is needed to refine diagnostic and treatment strategies for gastroduodenal pathology in CKD patients.